Urban Sprawl and Its Impacts on Land Cover Change in the Outskirts of the Surabaya Metropolitan Area - Rahmadani, Cut Sari Natasya; Zain, Alinda Fitriany Malik; Indraprahasta, Galuh Syahbana (Department of Urban and Regional Planning, Diponegoro University, 2025)
Development and economic growth in Indonesia have experienced rapid progress, followed by urbanization marked by the expansion of urban areas towards the outskirts, and have triggered urban expansion and land cover changes, especially on the outskirts of Surabaya City, and continue to expand to the Gerbangkertosusila area, which can indicate a decrease in Green Open Space (GOS). Given the important role of green open space in the sustainability of metropolitan areas, this study has three objectives. First, to analyze the impact of urban sprawl on GOS with spatial dynamics of land cover changes using Land Use Cover Changes (LUCC) analysis using ArcGIS software. Second, to identify spatial patterns of urban sprawl, and third, to calculate the index sprawl value to determine areas with urban sprawl impacts. The results of our study show that GOS has decreased in 25 years by 9.32%, and built-up area has increased by 8.27% of the total area of Gerbangkertosusila. The patterns of urban expansion that occur are Leap Frog Development, Ribbon Development, and Post- suburbia. The highest area expansion index value is in Sidoarjo at 4.74 and the lowest in Bangkalan at -7.62. The expansion of this area is marked by the development of settlements, industrial areas, and transportation routes, which result in the conversion of green open spaces into Built-up areas. Based on the analysis used in the Gerbangkertosusila area, the concept of Urban Growth Boundaries (UGB) is necessary; this concept effectively addresses urban expansion by establishing urban development permit policies.